Employee competence development in corporate volunteering. Issue 4 (16th June 2021) - Glińska-Neweś, Aldona; Hatami, Akram; Hermes, Jan; Keränen, Anne; Ulkuniemi, Pauliina
Abstract : Purpose: The purpose of this study is to examine how employee competences can be developed through corporate volunteering (CV). Specifically, this study focuses on diversity of volunteering studies categorized according to the type of beneficiaries and intensity of volunteer contact with them. The study examines how the beneficiary-employee relation influences the development of employee competences in CV projects. Design/methodology/approach: In this qualitative empirical study, interview data collected in Poland about the perceived effects of CV projects on employee competences was used. Findings: The findings suggest that to understand the competences generated in CV, attention needs to be paid to the nature of the volunteering study itself. The study proposes four different logics of competence development in CV, based on the type of the beneficiary and contact with them. Research limitations/implications: The study builds on managers' perceptions of competence development. For a holistic understanding, future research should include employees' perceptions of the process. Also, more research is needed regarding national and organizational settings as factors in competence development through CV. Practical implications: The study suggests how companies could best engage in volunteering programs and improve existing ones to make them more beneficial for all parties involved. Social implications: The findings build the better business case for CV and other corporate social responsibility (CSR) initiatives, i.e. they deliver rationales for business engagement in this regard. Originality/value: The study contributes to the conceptual understanding of CSR activities by presenting four logics of competence development in CV.